Pengaruh Kemampuan Kerja, Komitmen, Dan Motivasi Terhadap Kinerja Personel Polres Pamekasan - Yoni Evan Pratama (Jurnal Mahasiswa Manajemen dan Akuntansi, 2025)
This research was conducted at Pamekasan Police with a sample size of 85 personnel. The objectives of this study were 1). To describe the work ability, commitment, motivation and performance of Pamekasan Police personnel; 2). To test and analyze whether work ability, commitment and motivation simultaneously have an influence on the performance of Pamekasan Police personnel; 3). To test and analyze whether work ability, commitment and motivation partially have an influence on the performance of Pamekasan Police personnel; 4). To test and analyze which variables between work ability, commitment, work motivation have a dominant influence on the performance of Pamekasan Police personnel. Data analysis using SPSS, this type of research is explanatory research using a quantitative research approach. The results of the study indicate that: 1) Simultaneously, work ability, commitment, motivation have a significant influence on the performance of Pamekasan Police personnel; 2) Partially, work ability, commitment, motivation have a significant influence on the performance of Pamekasan Police personnel. Based on the results of the t-test, it is known that work ability has a dominant influence on the performance of Pamekasan Police personnel; furthermore 3) it is known that commitment has a positive and significant influence on the performance of Pamekasan Police personnel, and 4) motivation has a positive and significant influence on the performance of Pamekasan Police personnel.